2022
DOI: 10.1111/jcpe.13753
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis is associated with the development of fungal sinusitis: A nationwide 12‐year follow‐up study

Abstract: Aim The incidence of fungal sinusitis is increasing; however, its pathophysiology has not been investigated previously. We investigate the effect of periodontitis on the incidence of fungal sinusitis over a 12‐year follow‐up period using nationwide population‐based data. Materials and Methods The periodontitis group was randomly selected from the National Health Insurance Service database. The non‐periodontitis group was obtained by propensity score matching considering several variables. The primary end point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…From the asthma cohort (defined earlier), the control group was matched by 1:1 propensity score (PS) matching considering seven covariates, including the Charlson comorbidity index (CCI). We conducted PS matching using a "greedy nearest neighbor" algorithm with a 1:1 ratio (18)(19)(20)(21)(22)(23)(24). The success of PS matching was confirmed by standardized mean differences (SMDs) in each group (Table 1) (18)(19)(20)(21)(22)(23)(24).…”
Section: Study Design Studymentioning
confidence: 99%
See 1 more Smart Citation
“…From the asthma cohort (defined earlier), the control group was matched by 1:1 propensity score (PS) matching considering seven covariates, including the Charlson comorbidity index (CCI). We conducted PS matching using a "greedy nearest neighbor" algorithm with a 1:1 ratio (18)(19)(20)(21)(22)(23)(24). The success of PS matching was confirmed by standardized mean differences (SMDs) in each group (Table 1) (18)(19)(20)(21)(22)(23)(24).…”
Section: Study Design Studymentioning
confidence: 99%
“…We conducted PS matching using a "greedy nearest neighbor" algorithm with a 1:1 ratio (18)(19)(20)(21)(22)(23)(24). The success of PS matching was confirmed by standardized mean differences (SMDs) in each group (Table 1) (18)(19)(20)(21)(22)(23)(24). The initiation point for the study group was the date of the first asthma diagnosis, and that for the control group was the date of the first visit to the hospital from January 1, 2009.…”
Section: Study Design Studymentioning
confidence: 99%
“…To minimise this risk, we required sinusitis exposure to occur at least 1 year before disease onset. Sixth, unmeasured confounding is possible such as drug use (antibiotics, aspirin, non-steroidal anti-inflammatory drugs, anti-histamines), atopy, periodontitis 60 and healthcare utilisation. Finally, we performed multiple comparisons in this study, though each disease was prespecified in our protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, implant properties and implant status may affect development of fungus balls. Studies have shown that peri-implantitis in sinus floor augmentation may be related to maxillary sinusitis 28 and periodontitis is associated with increased risks of fungus balls (adjusted hazard ratio, 1.46; p = 0.002) 29 . Rough-surfaced implants promote osseointegration; however, the rough surfaces increase the risk of peri-implantitis 30 .…”
Section: Discussionmentioning
confidence: 99%